1984
DOI: 10.1203/00006450-198409000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Antioxidant Enzyme Maturation in the Fetal and Neonatal Rat. II. The Influence of Maternal Iron Supplements upon Fetal Lung Catalase Activity

Abstract: SummaryIt was obsegved that the lung catalase activity of premature (day 21 of gestation; term = 22 days) rat pups is affected by maternal iron intake. Pups from control dams receiving Purina Lab Chow and water ad libitum have only 50% of the lung catalase activity of pups from dams who received 1 mg/kg parenteral iron dextran daily from day 7 to day 20 of gestation. Other oxygen-protective enzymes, copper-zinc and manganese superoxide dismutase, glutathione peroxidase, and glucose-6-phosphate dehydrogenase, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…It is possible that the failure to increase CAT activity between d 20 and term in the fetal lung is a reflection of reduced iron transport across the placenta. The influence of maternal iron supplements on fetal lung catalase activity has been reported elsewhere (27). The perinatal changes in GPX activity were similar to those reported by Yam et al (33) as U/mg protein, but they reported a moderate increase in adult life that was not evident in our adult group.…”
Section: Discussionsupporting
confidence: 75%
“…It is possible that the failure to increase CAT activity between d 20 and term in the fetal lung is a reflection of reduced iron transport across the placenta. The influence of maternal iron supplements on fetal lung catalase activity has been reported elsewhere (27). The perinatal changes in GPX activity were similar to those reported by Yam et al (33) as U/mg protein, but they reported a moderate increase in adult life that was not evident in our adult group.…”
Section: Discussionsupporting
confidence: 75%
“…They found a similar developmental pattern for GSH-px, but the increase in CAT between days 20 and 22 and just after birth observed in the present investigation was not seen in their study. Since they have subsequently shown (27) that the CAT level in prenatal rat lung is highly influenced by the iron intake of the pregnant dams, the discordance between the results may possibly be explained by differences in the nutritional status of the animals in the two studies. The very moderate perinatal increase in total SOD (about 30%) in the present study fits well with the data of Tanswell and Freeman (26) if their CuZn-SOD (copper zinc-SOD) and Mn-SOD (manganese-SOD) values are combined to yield total SOD activity.…”
Section: Discussionmentioning
confidence: 99%